Prediksi Gaya Hambat Terhadap Jarak Jangkau Mortir 60 mm Dengan Jaringan Syaraf Tiruan - Slamet Widodo; M. Aziz Muslim; Didik R. Santoso (Jurnal EECCIS, 2015)
Analysis of the influence of drag force on the range of grenade 60 mm mortar is one approach to calculate the firing distance. Some methods can be used for calculating the 60 mm mortar firing range such that the aerodynamic and ballistic method. As performace reference, the firing book table of 60 mm mortar is used. This research aims to design and build software with neural network method to predict the drag that affects mortar firing range so that we will get the drag prediction. It will be used to perform calculations of the shooting range. Experimental results of drag prediction using a unit neural network with 2 input units, 4 hidden units and 1 output can produce the Mean Square Error (MSE) of 4,03x10-5. The prediction results can be used to determine the distance to achieve mortar although still not as precise as the firing table book with an average of 13.8013% error .Keywords: Mortars 60 mm, firing Book Table , Ballistic, Aerodynamics, Artificial Neural Networks